The Role of Social Media Toward Patient Satisfaction and Patient Loyalty in Private Hospitals - Rudy Kurniawan; Margaretha Pink Berlianto (Enrichment : Journal of Management, 2022)
It has been a challenge for hospitals to meet patient satisfaction with health services provided. There are many factors related to patient satisfaction, one of them is communication, especially in this digital era where the patients can access easily through social media. Not only communication between hospitals and patients, but also communication between patients and doctors play an important role. To address the underlying mechanism between these predictors in the context of social media and patient loyalty. This study used an observational-descriptive design with 302 respondents who have received a service from a private hospital either outpatient or inpatient. They are selected by simple purposive sampling. Data were collected using an online questionnaire. Data was analyzed using PLS-SEM. Patient trust toward hospital, strength of hospital patient communication, and perceived image of hospital are not associated with patient satisfaction. Perceived image of doctor is positively associated with patient satisfaction and patient satisfaction is positively associated with patient loyalty. In social media context, perceived image of doctor is positively associated with patient satisfaction. We need to improve patient satisfaction in order to increase patient loyalty.